2011
DOI: 10.1002/jbmr.366
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-targeted overexpression of PPARγ inhibited bone mass gain in male mice and accelerated ovariectomy-induced bone loss in female mice

Abstract: PPARg has critical role in the differentiation of mesenchymal stem cells into adipocytes while suppressing osteoblastic differentiation. We generated transgenic mice that overexpress PPARg specifically in osteoblasts under the control of a 2.3-kb procollagen type 1 promoter (Col.1-PPARg). Bone mineral density (BMD) of 6-to 14-week-old Col.1 À PPARg male mice was 8% to 10% lower than that of their wildtype littermates, whereas no difference was noticed in Col.1-PPARg female mice. Col.1-PPARg male mice exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 66 publications
(77 reference statements)
3
47
1
Order By: Relevance
“…For example, female rats treated with rosiglitazone did not exhibit any adverse effect on bone, while ovariectomy in these rats led to a significant rosiglitazone-induced bone loss, indicating that TZDs may enhance the bone loss induced by estrogen deprivation (Sottile et al 2004). This is in agreement with a recent study in transgenic mice overexpressing PPARg in osteoblasts, in which the bone loss in female became evident only after ovariectomy, although the male mice also exhibited reduced bone mass (Cho et al 2011). Clinical studies have also shown that TZDs have greater effects on bone loss (Berberoglu et al 2010) and risk of fractures (Kahn et al 2008) in postmenopausal women with type 2 diabetes than in males.…”
Section: Ampk and The Skeletal Effects Of Antidiabetic Drugssupporting
confidence: 90%
“…For example, female rats treated with rosiglitazone did not exhibit any adverse effect on bone, while ovariectomy in these rats led to a significant rosiglitazone-induced bone loss, indicating that TZDs may enhance the bone loss induced by estrogen deprivation (Sottile et al 2004). This is in agreement with a recent study in transgenic mice overexpressing PPARg in osteoblasts, in which the bone loss in female became evident only after ovariectomy, although the male mice also exhibited reduced bone mass (Cho et al 2011). Clinical studies have also shown that TZDs have greater effects on bone loss (Berberoglu et al 2010) and risk of fractures (Kahn et al 2008) in postmenopausal women with type 2 diabetes than in males.…”
Section: Ampk and The Skeletal Effects Of Antidiabetic Drugssupporting
confidence: 90%
“…Following OVX at 4 months old, C57BL/6J prostaglandin E2 receptor (one of the four prostanoid receptors) knockout mice exhibited protection against bone loss in femur and L4 vertebrae (31). However, when OVX was performed on 30-week-old female Col.1-PPARγ mice, ovariectomy-induced bone loss was accelerated (10). As the present results revealed that the factor age of C57BL/6J influenced the sensitivity of bone to OVX, the conclusions of a specific gene on osteoporosis must be identified with care.…”
Section: -Week-old ------------------------------------------------mentioning
confidence: 99%
“…However, compared with rats, mice may be a more effective model as they have a more easily manipulated genome and lower drug doses are required for treatment. Several strains of mice have been used in postmenopausal osteoporosis research (10)(11)(12)(13). However, there are controversies regarding the use of C57BL/6J mice as an animal model for postmenopausal osteoporosis (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Briefly, total BM cells from femora and tibiae were flushed out using a 27-gauge needle, and the resulting cells were cultured in an a-MEM supplemented with 10% FBS, 1% glutamine, and 30 ng/mL macrophage colony-stimulating factor (M-CSF) for 3 days. To induce osteoclast formation, BMMs were treated with M-CSF (30 ng/mL) and receptor activator of nuclear factor kappa-B ligand (RANKL; 50 ng/ mL) in the presence or absence of 0.5· or 1· hUCB-MSC CM in 96-well culture plates (Corning LifeSciences, Edison, NJ).…”
Section: In Vitro Effect Of Hucb-msc CM On Osteoclastic Differentiationmentioning
confidence: 99%